2020
DOI: 10.1002/aoc.5803
|View full text |Cite
|
Sign up to set email alerts
|

An imidazole functionalized copper(II)‐organic framework for highly selective sensing of picric acid and metal ions in water

Abstract: An imidazole functionalized metal–organic framework (MOF), [Cu(HL)(H2O)]·(H2O)·(DMA) (HBU‐166, H3L = 4,4′,4″‐(1H‐imidazole‐2,4,5‐triyl)tribenzoic acid, DMA = N,N‐dimethylacetamide) was synthesized and characterized by single‐crystal X‐ray diffraction. HBU‐166 was observed as a two‐dimensional MOF and showed good stability in water, an acidic solution (pH = 4), and an alkaline solution (pH = 9). HBU‐166 exhibited ligand‐based luminescence with a blue shift, which could be attributed to the coordination effect. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…45 Previous studies have shown that the introduction of imidazole as a functional group in molecules could achieve specific recognition of picric acid (PA) over various nitroaromatic compounds (NACs) by exhibiting a characteristic change in spectroscopy and/or luminescent color owing to the protonbinding nature of imidazole. [46][47][48] Since PA is considered a hazard that is widely used in powerful explosives, plasticizers, and pharmaceuticals, 49,50 the development of PA sensors in recent years has attracted considerable attention. A fluorescence titration assay was carried out to assess the sensing performance.…”
Section: Resultsmentioning
confidence: 99%
“…45 Previous studies have shown that the introduction of imidazole as a functional group in molecules could achieve specific recognition of picric acid (PA) over various nitroaromatic compounds (NACs) by exhibiting a characteristic change in spectroscopy and/or luminescent color owing to the protonbinding nature of imidazole. [46][47][48] Since PA is considered a hazard that is widely used in powerful explosives, plasticizers, and pharmaceuticals, 49,50 the development of PA sensors in recent years has attracted considerable attention. A fluorescence titration assay was carried out to assess the sensing performance.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these materials are kinds of 1D, 2D and 3D crystal materials formed by selfassembly of organic ligands (mainly aromatic compounds and azole compounds) with metal ions. [1][2][3][4] Imidazole, a kind of pentacyclic heterocyclic compound with one potential coordination nitrogen atom and three carbon atoms, [5][6][7][8][9] a kind of high nitrogen coordination compound, could be easy to coordinate with metal ions in a variety of coordination ways with a small volume. It also can reduce the steric hindrance and it is pentacyclic heterocyclic compound containing two potential coordination nitrogen atoms and three carbon atoms with relatively small volume, which may reduce steric hindrance and improve spatial bonding structure.…”
Section: Introductionmentioning
confidence: 99%
“…The 1D chain SBUs are further linked by the backbone of the H 3 L ligands to form a 3D framework structure with {3 5 9.4 8 2.5 12 } {3 6 4.4 8 3.5 6 } topology (Figure d). The porosity of HBU-168 is 0.3466 according to the calculation results …”
mentioning
confidence: 98%
“…Nitroaromatic compounds (NACs), metal ions, and dyes are frequently used in the processing of raw materials and synthesis of fine chemicals, pharmaceuticals, dyestuffs, spices, explosives, and pesticides; as a result, they are frequently released as waste, making them targets for sensing and adsorption. For example, p -nitrophenol is used to prepare the over-the-counter drugs paracetamol and phenacetin. The aromatic rings, such as phenyl rings, in NACs have characteristic electronic effects that can result in changes in the properties of MOFs upon interaction. , For example, aromatic compounds having electron-withdrawing nitro groups can result in the formation of an electron-deficient environment in the MOFs.…”
mentioning
confidence: 99%
See 1 more Smart Citation